ANALISIS IMPLEMENTASI APLIKASI MANAJEMEN HUBUNGAN PELANGGAN, STUDI KASUS PT NCI - Rusmanto Rusmanto (Jurnal Informatika Terpadu, 2015)
Good customer relationship management is needed by the marketing department of the company, including the company training services. The utilization of information technology for customer relationship management is becoming important due to the availability of the internet and other information technology products for today's marketing communications very wide. SugarCRM is a customer relationship management application that has been well implemented in various world companies and service companies in Indonesia. The analysis was conducted to find out the benefits of SugarCRM in a training service company using a case study of PT NCI. Companies that previously only used general office applications in Manually managing customer data to serve and maintain customer loyalty has proven to be better after using the SugarCRM application as a marketing information system for managing customer relations. Some of the improvements in the marketing department's performance include making it more accessible in collecting and accessing customer data, understanding customer expectations and desires, and providing services to customers, with the hope of increasing customer satisfaction and improving company income and profits. There are still some shortcomings that need to do further researched. Further research is also needed, among others, to compare SugarCRM with other similar applications.